Oosthoek Sugar Eden: The colonial sugar industry in Panaroekan - Maghfiroh, Nurul (Historiography: Journal of Indonesian History and Education, 2025)
Abstract Sugar has been indispensable in the global economy over the past nineteenth century. New lands were being explored to become sugar-producing areas, not least Panaroekan. During the colonial period, several sugar factories were constructed in Panaroekan. In addition, some of these sugar mills are still in operation. Based on this research background, this paper examines the history of the sugar industry in Panaroekan during the colonial period. In addition, this research also aims to identify the varying factors that drove the growing sugar industry in the region. This research will use the historical approach as a method to reconstruct events in the past. Based on the research conducted, it is known that the area's fertility and the existence of low-cost labor were the major factors that prompted the accelerated growth of the sugar industry in Panaroekan. This made the area an important sugar manufacturer in the Eastern part of Java. Abstrak Gula menempati posisi yang penting dalam perekonomian global di sepanjang abad ke sembilan belas. Daerah-daerah baru di eksplorasi menjadi kawasan penghasil gula tidak terkecuali Panaroekan. Pada masa kolonial didirikan beberapa pabrik gula di Panaroekan. Bahkan beberapa pabrik gula tersebut masih beroperasi hingga saat ini. Berdasarkan latar belakang tersebut, maka kajian ini membahas bagaimana perkembangan industri gula di Panaroekan selama periode kolonial. Selain itu, penelitian ini bertujuan untuk mengidentifikasi berbagai faktor yang mendorong pertumbuhan industri gula di wilayah tersebut. Penelitian akan menggunakan pendekatan sejarah sebagai metode untuk merekonstruksi peristiwa di masa lampau. Berdasarkan penelitian yang dilakukan diketahui bahwa kesuburan wilayah dan ketersediaan tenaga kerja yang murah menjadi faktor utama yang mendorong percepatan pertumbuhan industri gula di Panaroekan. Sehingga menjadikan kawasan ini sebagai penghasil gula yang penting di ujung timur Pulau Jawa.